OPA1-Exon4b Binds to mtDNA D-Loop for Transcriptional and Metabolic Modulation, Independent of Mitochondrial Fusion - Yang, Liang; Tang, Haite; Lin, Xiaobing; Wu, Yi; Zeng, Sheng; Pan, Yongzhang; Li, Yukun; Xiang, Ge; Lin, Yi-Fang; Zhuang, Shi-Mei; Song, Zhiyin; Jiang, Yiguo; et al. (Frontiers in Cell and Developmental Biology, 2020)
Optic Atrophy 1 (OPA1) has well-established roles in both mitochondrial fusion and apoptotic crista remodeling, and is required for the maintenance and distribution of mitochondrial DNA (mtDNA) which are essential for energy metabolism. However, the relationship between OPA1 and mitochondrial metabolism and the underlying mechanisms remain unclear. Here, we show that OPA1-Exon4b modulates mitochondrial respiration, and rescues inner mitochondrial membrane potential (m) independent of mitochondrial fusion. OPA1-Exon4b is required for the maintenance of normal TFAM distribution and enhances mtDNA transcription by binding the D-loop of mtDNA. Finally, we show that mRNA levels of OPA1 isoforms containing Exon4b are specifically downregulated in hepatocellular carcinoma (HCC), leading to a reduction in m. Thus, our study demonstrates a novel mitochondrial functional self-recovery pathway involving enhanced mtDNA transcription-mediated recovery of mitochondrial respiratory chain proteins. This mitochondrial fusion-independent pathway may contribute to mitochondrial multi-functional switches in tumorigenesis.